PENGARUH KEPUTUSAN PENDANAAN DAN KEADAAN PASAR MODAL YANG DI MEDIASI OLEH RISIKO KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2008-2012 - Ganda Nugraha; Yulia Efni; Haryetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The aim of the research is to test the direct and indirect effect of financing decision and capital market condition in mediated by risk toward firm value the company manufactures a variety of industrial sectors companies listed in Indonesia Stock Exchange (IDX) period 2008-2012. The population of the research is 54 company and the variety of industry sectors into a sample of 21 companies by N of data as much as 105. The sampling method used is based purposive sampling. Data analysis using descriptive analysis and path analysis. By path analysis, some important findings are obtained that financing decisions no significant influence directly toward company value. Capital markets condition directly is significant influence toward company value. Financing decisions no significant influence directly toward Financial risk. Capital markets condition directly is significantly influence toward Financial risk. Financial risk no significant influence direct toward company value. This means indirectly the financial risk is not able to mediate the relationship between financing decisions toward company value. And financial risks are also not able to mediate the relationship between the capital markets condition toward value of company.Keywords: Financing decision, capital markets condition and company value